Efektifitas Penggunaan Modul Berbasis Problem Base Learning Pada Mata Kuliah Telaah Naskah - Utami, Respati Retno; Andini, Agni Dhea; Istantiani, Meinita; Purnomo, Bambang (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
This study aims to determine the effectiveness of using Problem Based Learning-based modules in the text review course. This study took a sample of 4th semester students of class A class A, Regional Language and Literature Department, State University of Surabaya. The research method used is descriptive quantitative method. Data collection techniques were carried out by distributing questionnaires, observations, and giving test questions for cognitive learning outcomes. The data analysis technique was carried out with One Group Pretest-Posttest Design, then the data was tested using the normality test and T-Test (Paired Samples T-Test). The results showed that the Problem Based Learning-based module was effectively used in the manuscript review course. This is evidenced by the progress of the average score from pretest to posttest, namely from 64.1034 to 73.5517. The minimum score in the pretest is 50.00, with the maximum score being 78.00. It is different with the posttest, the minimum score achieved by students is 60.00 and the maximum score is 85.00. On the basis of these advances, the Problem Based Learning-based module is effective for improving students' understanding and skills in the text review course.